The Implementation of Cooperative Learning of Numbered Head Together (NHT) Efforts to Improve Activity and Learning Results of Class VII A Students on Subjects of ICT (Information and Communication Technology) of SMP Saraswati Singaraja at the Academic Year 2011/2012 - Suci Ariantini, Made (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
The classroom action research (CAR) was aimed at 1) improving the students’ activity through The Implementation of Cooperative Learning of Numbered Head Together; 2) improving the students’ learning results through The Implementation of Cooperative Learning of Numbered Head Together; 3) to know students’ responses towards through The Implementation of Cooperative Learning of Numbered Head Together. NHT has four stages, namely: the numbering (numbering), the questioning (questioning), to think together (heads together) and giving the answer (answering).The current research was a CAR in which the subjects of the study were the class VII A students of SMP Saraswati Singaraja at the academic year 2011/2012 with the object of the study being the students’ activity to learn, their learning results and students responses in the standard of competence to practice basic computer skills. Data collection activities using observation sheets, the learning to use the test results of quizzes, worksheets and tests student evaluation, students’ responses using a questionnaire. The learning activity data were collected using observation sheets, student learning outcome data obtained through the tests quizzes, group worksheet and evaluation tests. As for the student response data retrieval using a questionnaire. The results showed that: 1) there was increased activity of student learning outcomes, it can be seen from the average yield earned on learning activity cycle of 12.5 with a category I active enough while in the second cycle of 15.2 with the active category; 2) the average grade has increased by 20% ie from 68 in cycle I to 86 in the second cycle to complete qualifications, while the classical completeness of the cycle I increased by 39% to 86% in cycle II; 3) students’ response to the application of cooperative learning model of NHT on the subjects of ICT, especially in the standard of competence to practice basic computer skills is positive with an average of 44.